АНТИТЕТИЧНІ ВІДНОШЕННЯ У ТЕКСТІ РОМАНУ ЛОНГА - Chakal (Makar), Inesa (Видавничий дім Дмитра Бураго, 2014)
In the article the stylistic figure of antithesis is described in the text of the pastoral novel of ancient greek writer Longus (2nd century A.D.) “Daphnis and Chloe”. The role of antonyms in creation of antitheses is defined. Notwithstanding that antithesis is not the dominant feature of Longus’ idiostyle, yielding according frequency to different stylistic figures, tropes, it shows itself as a striking expressive mean, capable of taking part in formation of author’s idiostyle. У статті охарактеризовано стилістичну фігуру антитезу в тексті пасторального роману давньогрецького письменника ІІ ст. н.е. Лонга „Дафніс і Хлоя”. З’ясовано роль антонімії у творенні антитез. Виокремлено декілька типів антитетичних структур: прості, складносурядні, складнопідрядні та безсполучникові речення. Незважаючи на те, що антитеза не є домінантною рисою ідіостилю Лонга, уступаючи за частотністю іншим стилістичним фігурам, тропам, вона є яскравим виразним засобом, здатним брати участь у формуванні ідіостилю автора.
Antithetical relations in the text of Longus’ novel
Keywords: antonyms; antithesis; antithetical relations; idiostyle; ancient Greek novel; Longus; антоніми; антитеза; антитетичні відношення; ідіостиль; давньогрецький роман; Лонг; Дафніс і Хлоя